A new species of the genus Microcavia (Rodentia, Caviidae) - Teta, Pablo; Jayat, J. Pablo; Ortiz, Pablo E. (THERYA, 2021)
Based on qualitative and quantitative morphological evidence, we describe a new species of Microcavia (Rodentia, Caviidae). The new species is characterized by a unique combination of morphological traits, that distinguished it from all others within the genus (i. e., upper incisors moderately proodont; palatal crest low, narrow anteriorly and expanded posteriorly; paraorbital process of the jugal small; sphenopalatine vacuities small, with their anterior border located behind the anterior half of the mesopterygoid fossa). The new species seems to be endemic from northwestern Argentina, where it occurs in open shrublands and grasslands >3,100 masl. With the description of this taxon, there are already four species of Microcavia that are distributed in the central Andes.